2009
DOI: 10.1111/j.1365-2702.2008.02721.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse staffing, quality of nursing care and nurse job outcomes in intensive care units

Abstract: Adequate staffing must be assured to achieve better quality of care and job outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(123 citation statements)
references
References 28 publications
(65 reference statements)
2
113
0
8
Order By: Relevance
“…Among almost 1400 Korean ICU nurses, only one fifth felt that there were enough nurses to provide quality care. One third were dissatisfied, half were burned out and a quarter planned to leave within the year (Cho et al, 2009). Almost 6000 Japanese nurses in another study revealed high burnout-levels; six in ten expressed dissatisfaction with their jobs and a similar proportion reported that quality in their unit could be considered fair or poor (Kanai-Pak et al, 2008).…”
Section: Health Professional Burnout and Qualitymentioning
confidence: 99%
“…Among almost 1400 Korean ICU nurses, only one fifth felt that there were enough nurses to provide quality care. One third were dissatisfied, half were burned out and a quarter planned to leave within the year (Cho et al, 2009). Almost 6000 Japanese nurses in another study revealed high burnout-levels; six in ten expressed dissatisfaction with their jobs and a similar proportion reported that quality in their unit could be considered fair or poor (Kanai-Pak et al, 2008).…”
Section: Health Professional Burnout and Qualitymentioning
confidence: 99%
“…In addition, not only patients may be harmed, but also the nursing staff may suffer from burnout [13,14], affecting the intent to leave and staff turnover [13]. Nevertheless, overstaffing can lead to a dissipation of funds, which is unacceptable in times of rising demand for efficiency savings.…”
Section: Introductionmentioning
confidence: 99%
“…One large prospective study of 2323 ICU nurses found associations between intention to leave and professional status ( x = 2.20, SE 0.08; p < .001), nursing leadership ( x = 2.24, SE 0.08; p < .001), staffing and resource adequacy ( x = 2.27, SE 0.06; p < .001), nursing foundations ( x = 2.34, SE 0.06; p < .001), nurse-physician collegiality ( x = 2.51, SE 0.06; p < .001) and rostering flexibility ( x = 2.48, SE 0.09; p < .001) [3] . These associations were also found two ICU studies [48,54] and five studies in acute care settings [42,46,51,55,56] .…”
Section: Intention To Leavementioning
confidence: 54%
“…Emotional exhaustion was explored in fifteen studies, three in ICU [50,52,54] . A significant association was consistently reported between the level of emotional exhaustion, or burn out, by nursing staff.…”
Section: Emotional Exhaustionmentioning
confidence: 99%
See 1 more Smart Citation